Price Cost of Production in SMEs Factory Abadi Jaya Crackers - Darmansyah Hegi Pranoto; Zaidan Rahadian; Dwi Epty Hidayaty (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the businesses that processes snacks is Kerupuk Abadi Jaya which is located at Jl. Ir. Jatirasa, Kec, Haji Juanda Gang Makmur No. 25 Karawang, Cikampek, West Java Due to a lack of understanding of calculations, these UMKM have not been able to calculate the Cost of Production. As a result, various attempts were made to overcome this problem. In this study, we will use Microsoft Word software to calculate the Cost of Production using digital recording forms using the Software. Of course, using this software will make it easier to report production costs and calculate production costs. The recording includes the costs of Kerupuk Abadi Jaya production, such as raw material costs, factory overhead costs, and labor. We estimate that business actors will find out how much it costs to produce Kerupuk Abadi Jaya, from raw materials to finished goods, by calculating the Cost of Production. so that UMKM can develop into advanced and long-lasting businesses in the future